Mun'im Sirry's Middle Path: Bridging Revisionist and Traditionalist Perspectives in Qur'anic Scholarship - Abad Badruzaman; Rizqa Ahmadi; Syahril Siddik (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2024)
This article addresses the ongoing debate of the reliability of the Qur'an as a historical source, focusing on the codification and stabilization of its text. This research examines several significant works by Mun'im Sirry that have contributed to Qur'anic scholarship while raising controversies, particularly among Southeast Asian scholars. Sirry’s critical approach situates his thoughts within the broader discourse of traditionalist and revisionist streams in Qur'anic studies. This study employs a qualitative library research method, cross-referencing Qur'anic scholarship to investigate Sirry's contributions. By comparing his thoughts with both traditionalist and revisionist views, the study aims to assess Sirry’s position and its impact on debates surrounding the historical authenticity of the Qur'an. The findings reveal that Sirry bridges the gap between the extreme skepticism of revisionists and the uncritical acceptance of traditionalists. His nuanced stance acknowledges both the textual evolution of the Qur'an and its historical significance. The study contributes to the ongoing debates on Qur'anic codification, revealing Sirry's role as a critical yet balanced scholar who navigates between these two extremes. His approach emphasizes the importance of historical-critical methods while also recognizing the roles of key figures, such as Abdul Malik and Hajjaj, in stabilizing the Qur'an’s text. Sirry’s position fosters a deeper understanding of the Qur'an’s role in Islamic history, offering a middle path that challenges both traditionalist and revisionist interpretations.